Breaking Bureaucratic Barriers: How Public Service Motivation Drives Employee Performance in the Digital Age - Fitriani, Arbania; Jaya, Wihana Kirana; Sumaryono , Sumaryono; Rosari, Reni; Situmorang, Dominikus David Biondi; Ifdil, Ifdil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
This study examines the complex interplay among Public Service Motivation (PSM), red tape, and work-related outcomes within Indonesia's public sector, utilizing a sample of 2,386 state-owned enterprise employees. Employing Partial Least Squares Structural Equation Modeling, we analyze PSM's influence on work engagement, affective commitment, and innovative work behavior while assessing red tape's moderating role. Our findings reveal that PSM significantly enhances work engagement and affective commitment. However, PSM does not directly predict innovative work behavior, suggesting innovation requires additional organizational support. Red tape negatively impacts engagement, commitment, and innovation, underscoring the need for process simplification. Work engagement mediates the relationship between PSM and affective commitment and innovation, highlighting its pivotal role. Notably, red tape does not moderate PSM’s effect on engagement, indicating PSM's resilience amid bureaucratic constraints. These insights emphasize the importance of fostering PSM to strengthen employee commitment and engagement. Additionally, policymakers must address bureaucratic inefficiencies and cultivate innovation-supportive environments to enhance public sector governance effectiveness.